LEGAL ANALYSIS OF THE LEGALITY OF MODIFYING AND RESELLING CREATIVE COMMONS-LICENSED DIGITAL PRODUCTS - Firman Nurdiyansyah Sunandar; Andri Herman Setiawan; Ahmad Juaeni; Johannes Triestanto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The rapid proliferation of digital markets has intensified legal challenges surrounding the modification and resale of Creative Commons–licensed digital products in Indonesia. This study conducts a doctrinal analysis of the Indonesian Copyright ActLaw No. 28 of 2014) in light of comparative jurisprudence from Japan, Taiwan, and the United States, elucidating how civil-law and common-law systems treat CC licenses. It examines recurring issues ambiguities in “derivative works,” conflicts between non-commercial and commercial exploitation clauses, and failures to observe attribution requirements through practical case studies of software, e-books, music, and video tutorials. Drawing on Satjipto Rahardjo’s progressive legal theory, the research argues for a functional, transformative approach that aligns domestic copyright doctrine with globally harmonized open-licensing principles and substantive justice. The analysis reveals that, under Indonesian law, permissibility hinges on strict adherence to each license’s specific terms; however, current regulations lack clarity, generating legal uncertainty for both creators and users. To address these gaps, the study proposes interpretative guidelines and legislative reforms that (1) define “derivative works” in accord with CC International’s porting model, (2) reconcile non-commercial provisions with legitimate digital markets, and (3) institutionalize attribution standards. Such measures would safeguard creators’ moral and economic rights while fostering equitable digital access and innovation, thereby enhancing Indonesia’s knowledge economy.